Preparing Preservice Teachers to Address Bullying through Cartoon Lessons - Rule, Audrey C.; Logan, Stephanie R.; Kohler, Frank W. (Journal of the American Academy of Special Education Professionals, 2013)
Students who qualify for special education services are at risk for being bullied because of their cognitive, emotional, behavioral, or physical differences. Currently, teachers are not effective enough in reducing bullying; better preservice teacher preparation in this area may help to alleviate the problem. The current study explored the effects of preservice teachers using cartoons to spark discussion of bullying issues during practicum experiences with elementary students at urban schools. Twenty-one preservice special education teachers participated in the mostly qualitative study that presented an analysis of their reflections after teaching three cartoon-focused lessons on bullying to students in small groups, each containing at least one student with special needs. Reflections revealed the success of the cartoon lessons with positive effect on classroom climate. Preservice special education teachers became aware of the motivating effects of cartoons, the pervasiveness of bullying and the eagerness of elementary students to discuss it.